14C Analysis and Sample Preparation at the New Bern Laboratory for the Analysis of Radiocarbon with AMS (LARA). Issue 2 (2014) - Szidat, Sönke; Salazar, Gary A; Vogel, Edith; Battaglia, Michael; Wacker, Lukas; Synal, Hans-Arno; Türler, Andreas
Abstract : The University of Bern has set up the new Laboratory for the Analysis of Radiocarbon with AMS (LARA) equipped with an accelerator mass spectrometer (AMS) MICADAS (MIni CArbon Dating System) to continue its long history of 14 C analysis based on conventional counting. The new laboratory is designated to provide routine 14 C dating for archaeology, climate research, and other disciplines at the University of Bern and to develop new analytical systems coupled to the gas ion source for 14 C analysis of specific compounds or compound classes with specific physical properties. Measurements of reference standards and wood samples dated by dendrochronology demonstrate the quality of the 14 C analyses performed at the new laboratory.